The promise of generative Artificial lntelligence. Psychological implications in educational contexts - MIRAGLIA, Laura (Rivista di Scienze dell'Educazione, 2025)
The integration of Conversational Generative Artificial Intelligence into educational settings has generated both excitement and caution due to their potential to revolutionize learning experiences. This paper explores the dual nature of AI advancements, highlighting both their promises and challenges. It examines the role of AI-powered chatbots, exemplified by ChatGPT, in enhancing critical thinking, problem-solving, and decision-making skills among students. The paper examines the implications of equipping AI chatbots with Theory of Mind capabilities to enhance their credibility as interlocutors, emphasizing the potential for personalized learning and cognitive scaffolding. While advocating for strategies to integrate AI technologies into schools, such as new school subjects and “incorporating” ChatGPT into robots, the paper underscores the need for further research. In conclusion, it is recommended that educators, teachers, and parents be trained in the effective utilization of AI technologies in the classroom. This will empower students to flourish in an increasingly digitalized world. L’integrazione dell’Intelligenza Artificiale Generativa Conversazionale nei contesti educativi ha generato sia entusiasmo che cautela per il suo potenziale di rivoluzionare le esperienze di apprendimento. Questo articolo esplora la duplice natura dei progressi dell’IA, evidenziandone sia le promesse che le sfide. Esamina il ruolo delle chatbot alimentate dall’IA, esemplificate da ChatGPT, nel sostenere lo sviluppo del pensiero critico, delle capacità di problem-solving e dei processi decisionali degli studenti. L’articolo esamina le implicazioni di dotare le chatbot Al con capacità di Teoria della Mente con il fine di migliorare la loro credibilità come interlocutori, sottolineando il potenziale di apprendimento personalizzato e di scaffolding cognitivo. Pur sostenendo le strategie per integrare le tecnologie IA nelle scuole attraverso nuove materie scolastiche e l’”incorporazione” di ChatGPT nei robot, l’articolo sottolinea la necessità di ulteriori ricerche. In conclusione, si raccomanda che educatori, insegnanti e genitori siano formati all’utilizzo efficace delle tecnologie di IA in classe. Questo permetterà agli studenti di crescere in un mondo sempre più digitalizzato. La integración de la Inteligencia Artificial Generativa Conversacional en los contextos educativos ha generado tanto entusiasmo como cautela por su potencial de revolucionar las experiencias de aprendizaje. Este artículo explora la doble naturaleza de los progresos de la IA, poniendo en evidencia ya sean las promesas, ya sean los desafíos. Examina el papel de las chatbot alimentadas por IA, en el sostenimiento del pensamiento crítico, de las capacidades de resolución de problemas y de los procesos de toma de decisiones de los estudiantes. El artículo examina las implicaciones de la dotación del chatbot IA con la capacidad de Teoría de la Mente con el fin de mejorar su credibilidad como interlocutores, sosteniendo el potencial de aprendizaje personalizado y de andamiaje cognitivo. Aun sosteniendo las estrategias para integrar las tecnologías de IA en las escuelas a través de nuevas materias escolares y de la “incorporación” de ChatGPT en los robots, el artículo subraya la necesidad de investigaciones ulteriores. En conclusión, se aconseja que los educadores, los docentes y los padres se formen en el uso eficaz de las tecnologías de IA en clase. Esto permitirá a los alumnos crecer en un mundo cada vez más dominado por la digitalización.